Love and other consolation prizes : a novel - Ford, Jamie (New York : Ballantine Books, 2017)
"Inspired by a true story, this is the unforgettable story of a young boy named Ernest, set during the 1909 Seattle world's fair called the Alaska Yukon Pacific Expo. It is a time when the magical wonders of technology on display at the expo future seems limitless. But for Ernest, a half-Chinese orphan who found his way to America through a last desperate act of his beloved mother, every door is closed. A charity student at a boarding school, he has never really had a place to call home. Then one day, his wealthy sponsor announces that if a home is what he wants, then that is what he will have: Ernest will be offered as a prize in the daily raffle at the fair, advertised as "Healthy boy to a good home for the winning ticket holder." The woman who "wins" him is the madam of a notorious brothel who was famous for educating her girls. He becomes a houseboy in her brothel and is befriended by the daughter of the madam, as well as a Japanese girl who works in the kitchen. The friendship and love between these three form the first real family Ernest has ever known"--
Keywords: Families -- Fiction; Brothels -- Fiction; Friendship -- Fiction; FICTION / Literary; Domestic fiction